A study on dividend policy and value of the firm: managerial perspectives in Malaysia - Timothy Edward, Oswald; Hong Heng, Chu; Gee Choon, Lau (Unit Penyelidikan, Pembangunan Dan Pengkomersilan, 2005)
This study investigates the views of corporate managers about the relationship between dividend policy and value; explanations of dividend relevance including the bird-in-the hand, signaling, tax-preference, and agency explanations; and how firms determine the amount of dividends to pay. We obtain data from 2004 mail survey sent to 207 chief financial officers/financial controller/corporate managers of firms listed on the Bursa Malaysia. Based on 64 usable responses, the empirical result show that most survey respondents believe that dividend policy affects firm value. Of the four explanations for dividend relevance, the respondents generally express the highest level of agreement with statements about signaling. The results also show that managers are concerned about the continuity of dividends when setting dividend payments